“Exploring Deafhood”: Investigating the experiences of d/Deaf and Hard of Hearing people who faced barriers to Deaf culture - Koncovy, Jules (My University, 2023)
Throughout the literature, there is existing research on the experiences of people in the Deaf community from a culturally Deaf perspective and from a medicalized perspective of the condition of hearing loss; however, there is very literature on the experiences of people who do not fall within either of these binary views of what being d/Deaf and HoH is. This research aims to build upon existing literature and explore the experiences of d/Deaf and HoH people who grew up in Southern Ontario and were raised outside of the d/Deaf and Hard of Hearing community, and/or without access to signed language. This research is theoretically underpinned by critical disability theory and deaf critical theory—otherwise known as deaf crit—to broadly understand the nuances of how d/Deaf and HoH people are impacted by structural, systemic, and interpersonal experiences of audism, power, and oppression. This study relied on Photovoice as the research methodology to best center the perspectives of the participants through visual and textual analysis. Three participants participated in four virtual Photovoice workshops where they shared photographs in response to different prompts about their experiences as d/Deaf and HoH people. The ensuing discussion found the key themes: 1) the ability to explore their self-identity as d/Deaf and HoH people; 2) the importance of developing pathways to community early on in life; 3) the need for multiple supports when receiving care. This research contributes to the literature that centers the nuanced perspectives of those who are d/Deaf and HoH but raised without access to Deaf culture, community, and/or sign language and makes suggestions for future practice and policy that centers diverse needs and desires for support.
This research aims to build upon existing literature and explore the experiences of d/Deaf and HoH people who grew up in Southern Ontario and were raised outside of the d/Deaf and Hard of Hearing community, and/or without access to sign language.
Keywords: deaf; Deaf; Hard of Hearing; community access; Photovoice